1996
DOI: 10.1183/09031936.96.09040821
|View full text |Cite
|
Sign up to set email alerts
|

Long-, intermediate- and short-term growth studies in asthmatic children treated with inhaled glucocorticosteroids

Abstract: During recent years, new auxological techniques have been introduced for assessment of the risk of growth suppression in asthmatic children treated with exogeneous glucocorticosteroids. Assessment of lower leg growth rates with the knemometer has made short-term studies of growth processes under strictly controlled conditions possible. However, short-term lower leg growth rates cannot be used for estimations of intermediate-term height growth rates or long-term evaluations of final height. Consequently, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 68 publications
0
40
0
1
Order By: Relevance
“…Thus, new therapeutic approaches for the treatment of allergic diseases could be aided by the development of anti-eosinophilic tools. At present, the most effective pharmacological approach for severe eosinophilic reactions, such as asthma, comprises glucocorticoid therapy (4,5). However, steroids display a wide range of unwanted side effects.…”
mentioning
confidence: 99%
“…Thus, new therapeutic approaches for the treatment of allergic diseases could be aided by the development of anti-eosinophilic tools. At present, the most effective pharmacological approach for severe eosinophilic reactions, such as asthma, comprises glucocorticoid therapy (4,5). However, steroids display a wide range of unwanted side effects.…”
mentioning
confidence: 99%
“…In another study (56) , comprising 43 youngsters with mild asthma and ages between 7 and 14 years, the same authors observed that only the use of 800µg/day of budesonide caused a decrease in leg growth. In a third study (57) , they compared the use of 200µg/day of fluticasone with beclometasone dipropionate at doses of 400 e 800µg/day, in 19 children and adolescents aged from 7 to 14 years.…”
Section: Inhaled Corticosteroids and Growthmentioning
confidence: 81%
“…Measurements are usually made once a week, allowing to demonstrate and quantify the influence of a given drug on growth. This method, however, does not allow to make a prognosis about adult height (52)(53)(54) .…”
Section: Inhaled Corticosteroids and Growthmentioning
confidence: 99%
“…This short-term measure bears no relation to intermediate-or longterm growth of statural height. 15,16 Side effects such as adrenal suppression or effects on growth can be studied only through appropriate clinical measurements of adrenal function or height. Our finding of definite systemic steroid activity makes future studies of growth and adrenal function in young children on ICS imperative.…”
Section: Discussionmentioning
confidence: 99%